Industrial relations developments in Europe 2007 (Dublin, 2008)
"This annual review highlights the most significant developments in industrial relations in the EU Member States and Norway in 2007, both at national and EU level. It sets out the political context, then goes on to examine collective bargaining trends on pay, working time, equal opportunities and other topics. It outlines the year’s main developments in the following areas: employment legislation, social dialogue, and industrial action. The final chapter examines the impact of the European Directive establishing a general framework for informing and consulting employees in the European Communities.The study was compiled on the basis of individual national reports submitted by the EIRO correspondents. The text of each of these national reports is available below. The reports have not been edited or approved by the European Foundation for the Improvement of Living and Working Conditions. The national reports were drawn up in response to a questionnaire and should be read in conjunction with it."